'I don't think they trust the choices I will make.' – Narrative analysis of choice and control for people with psychosocial disability within reform of the Australian Disability Employment Services program. Issue 1 (2nd January 2021) - Devine, Alexandra; Dickinson, Helen; Brophy, Lisa; Kavanagh, Anne; Vaughan, Cathy
ABSTRACT: This paper explores New Public Management-inspired reforms to Australia's Disability Employment Services (DES), which assume increasing participant choice and control within DES will enhance provider competition and effectiveness. However, capability for exercising choice within this context is multifaceted. This is particularly so for participants who experience significant barriers to employment, as highlighted in our narrative analysis of the perspectives of DES participants with psychosocial disability and their resistance to exercising control to change providers despite dissatisfaction with outcomes. This brings into question whether increased marketization of DES will indeed support its objective of improving employment outcomes for people with disability.